Cognitive interpretation of the concept of “father” - Ochilova Noila Farmonovna (Zien Journals, 2025)
Nowadays, various areas of language are developing in modern linguistics. We can give an example of the human factor as the main factor in this. A new approach to the human factor in World linguistics, new areas that are developing today, in particular, scientific research in the fields of cognitive linguistics, cultural, pragmatics, sociolinguistics, ethnolinguistics, are considered related to language. To determine the nature of various phenomena requires a wide-ranging analysis from an anthropological point of view
Keywords: approach; concept; discourse